Management of complicated choledochal cyst in children: ultrasound-guided percutaneous external drainage and subsequent definitive operation - Jiayu Yan; Chuankai Lv; Dan Zhang; Mingkang Zheng; Chunhui Peng; Wenbo Pang; Wei Chen; Siwei Wang; Xiaoman Wang; Yajun Chen (BMC, 2023)
Abstract Objective The purpose of this study was to analyze the outcomes of the combination of ultrasound (US)-guided percutaneous external drainage and subsequent definitive operation to manage complicated choledochal cyst in children. Methods This retrospective study included 6 children with choledochal cyst who underwent initial US-guided percutaneous external drainage and subsequent cyst excision with Roux-en-Y hepaticojejunostomy between January 2021 and September 2022. Patient characteristics, laboratory findings, imaging data, treatment details, and postoperative outcomes were evaluated. Results Mean age at presentation was 2.7 ± 2.2 (0.5-6.2) years, and 2 patients (2/6) were boys. Four patients (4/6) had a giant choledochal cyst with the widest diameter of ≥ 10 cm and underwent US-guided percutaneous biliary drainage on admission or after conservative treatments. The other 2 patients (2/6) underwent US-guided percutaneous transhepatic cholangio-drainage and percutaneous transhepatic gallbladder drainage due to coagulopathy, respectively. Five patients (5/6) recovered well after US-guided percutaneous external drainage and underwent the definitive operation, whereas 1 patient (1/6) had liver fibrosis confirmed by Fibroscan and ultimately underwent liver transplantation 2 months after external drainage. The mean time from US-guided percutaneous external drainage to the definitive operation was 12 ± 9 (3-21) days. The average length of hospital stay was 24 ± 9 (16-31) days. No related complications of US-guided percutaneous external drainage occurred during hospitalization. At 10.2 ± 6.8 (1.0-18.0) months follow-up, all patients had a normal liver function and US examination. Conclusions Our detailed analysis of this small cohort suggests that US-guided percutaneous external drainage is technically feasible for choledochal cyst with giant cysts or coagulopathy in children, which may provide suitable conditions for subsequent definitive operation with a good prognosis. Trial registration Retrospectively registered.